การนำส่งและการแพร่กระจายของเคอร์คูมินในเนื้อเยื่อผิวผ่านเข็มระดับไมครอนชนิดละลายได้ของโพลีไวนิลไพโรลิโดนและกรดโพลีอะคริลิก - ปฐมาวดี เทพสาร (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
Injections through the skin using a hypodermic needle have many limitations, including painful injection, scarring, and producing of hazardous medical waste. However, the development of micro-sized needles called microneedles has overcome these limitations by reducing pain, scarring, and generating less hazardous medical waste. In this research, we have fabricated detachable dissolvable microneedles (DDMNs) using a molding method with polyvinylpyrrolidone (PVP) and polyacrylic acid (PAA) in an ethanol solvent and using curcumin as a model drug instead of hydrophobic drugs. By studying the ratio between PVP/curcumin, PAA/curcumin, and PVP/PAA/curcumin to determine the optimum ratio for fabricated microneedles that maximize the highest curcumin loading into the microneedle and are still strong enough to penetrate through the skin tissue. According to our research, a PVP/PAA ratio of 3/1 can load curcumin up to 12% (w/w). Additionally, our tests on the mechanical strength properties have shown that curcumin improves the mechanical strength of the needle, while the presence of PAA has reduced the mechanical strength of the needle. The experiment using ex vivo porcine skin revealed the successful delivery of curcumin into skin tissues and the delivered curcumin could diffuse in tissue.